Seizure outcomes and prognostic factors in patients with gangliogliomas associated with epilepsy - Hu, Yue; Zhang, Huawei; Adilijiang, Aihemaitiniyazi; Zhou, Jian; Guan, Yuguang; Qi, Xueling; Wang, Mengyang; Wang, Jing; Wang, Xiongfei; Liu, Changqing; Luan, Guoming (Frontiers in Surgery, 2022)
Introduction: Ganglioglioma (GG) patients often present with seizures. Although most patients can be seizure-free after tumor resection, some still experience seizures. The present study aimed to analyze a group of GGs patients associated with epilepsy and evaluate the seizure outcomes and prognostic factors. Methods: This retrospective study involved clinical data collected from medical records of patients diagnosed with GG pathologically and underwent surgical resection in Sanbo Brain Hospital, Capital Medical University. The seizure outcomes were evaluated based on the International League Against Epilepsy (ILAE) seizure outcome classification. The prognostic factors were identified according to univariate and multivariate analysis. Results: A total of 222 patients were included, with a mean age at surgery of 19.19 ± 10.93 years. All patients were followed up at least for one year with a mean follow-up duration of 6.28 ± 3.17 years. At the final follow-up, 174 (78.4%) patients achieved ILAE Class 1 or 2. Univariate and multivariate analyses revealed that the short duration of seizures and gross total resection were significant positive factors for seizure-free. Bilateral interictal or ictal epileptiform discharges in preoperative video-electroencephalogram (VEEG) were related to poor seizure outcomes. Conclusion: Surgical resection is an effective treatment for patients with epilepsy associated with GGs. The analysis of predictive factors could effectively guide clinical practice and evaluate the prognosis of epilepsy with GG.